1997
DOI: 10.1093/jjco/27.3.166
|View full text |Cite
|
Sign up to set email alerts
|

Second-line chemotherapy for relapsed small cell lung cancer

Abstract: Between January 1985 and August 1991, 159 patients with small cell lung cancer received first-line chemotherapy and 123 (77%) were responders. Of these, 88 relapsed, the remainder having died of other or unknown diseases or being alive without carrying cancer. The relapsed patients were examined to evaluate the outcome of the treatment for relapsed small cell lung cancer and to identify the factors that would contribute to the response rates and the survival durations. Forty-eight of 88 relapsed patients recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 8 publications
1
28
0
1
Order By: Relevance
“…6,7 For example, a prospective randomized trial comparing oral topotecan with best supportive care (BSC) revealed the benefits of treatment with oral topotecan in terms of the survival and quality of life. 7 Although some studies have shown the importance of both response and the duration of the response to initial chemotherapy in predicting the efficacy of second-line chemotherapy, [8][9][10] the number of studies conducted to identify the prognostic factors in recurrent SCLC patients is quite limited. In this retrospective study, we investigated the prognostic factors in recurrent SCLC patients administered second-line chemotherapy to determine the factors that need to be used for stratifying the patients in future clinical trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 For example, a prospective randomized trial comparing oral topotecan with best supportive care (BSC) revealed the benefits of treatment with oral topotecan in terms of the survival and quality of life. 7 Although some studies have shown the importance of both response and the duration of the response to initial chemotherapy in predicting the efficacy of second-line chemotherapy, [8][9][10] the number of studies conducted to identify the prognostic factors in recurrent SCLC patients is quite limited. In this retrospective study, we investigated the prognostic factors in recurrent SCLC patients administered second-line chemotherapy to determine the factors that need to be used for stratifying the patients in future clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown the importance of both response and the duration of the response to initial chemotherapy in predicting the survival of recurrent SCLC patients receiving second-line chemotherapy, [8][9][10] and currently it is widely accepted that recurrent SCLC patients should be classified into 2 groups: cases with sensitive recurrence and those with refrac- tory recurrence. 12 In contrast, Sundstrom et al, who recently analyzed 19 clinical factors at both the time of initial diagnosis and the time of recurrence, have suggested that the PS at the time of disease recurrence, and not the sensitivity status to first-line chemotherapy, was the only significant prognostic indicator for survival after second-line chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Relaps gözlenen hastalarda ikinci hat kemoterapi ile elde edilen sağkalım aslında birinci hat kemoterapiye alınan yanıtla ilişkilidir. Etkin bir kemoterapi sonrası objektif yanıt alınan ve 3 ay ya da daha uzun süre sonunda progresyon gözlenen hastalarda ikinci hat kemoterapiye daha iyi yanıt alındığı gösterilmiştir (5,11). KHAK'de uygulanan ikinci hat kemoterapi için genel kabul görmüş bir yaklaşım bulunmamaktadır.…”
Section: Discussionunclassified
“…At the time of recurrence, the tumour is broadly resistant to second-line chemotherapy and is lethal within a few to several months (Glisson, 2003). The further development of not only first-line chemotherapy but also of effective salvage chemotherapies is needed.In predicting the efficacy of salvage chemotherapy, two major factors are important: the response to the initial chemotherapy and the duration of time between the last exposure to chemotherapy and the confirmation of recurrence (Postmus et al, 1987;Giaccone et al, 1988;Ardizzoni et al, 1997;Ebi et al, 1997). Based on these factors, relapsed SCLC is now commonly classified into two main groups.…”
mentioning
confidence: 99%
“…In predicting the efficacy of salvage chemotherapy, two major factors are important: the response to the initial chemotherapy and the duration of time between the last exposure to chemotherapy and the confirmation of recurrence (Postmus et al, 1987;Giaccone et al, 1988;Ardizzoni et al, 1997;Ebi et al, 1997). Based on these factors, relapsed SCLC is now commonly classified into two main groups.…”
mentioning
confidence: 99%